The Effectiveness of the Use of Academic Information Systems - Nasaruddin H; Shofian Shofian; Haedar Akib; Risma Niswaty (Universitas Negeri Makassar, 2021)
Use information technology is used as a means that can facilitate a person or an agency in carrying out their work effectively and efficiently. This research is a qualitative descriptive study that aims to determine how effective the use of academic information systems is in the Office Administration Education Study Program, Faculty of Social Sciences, Universitas Negeri Makassar. The informants of this research are all parties who are directly involved in the use of academic information systems, namely students, study program operators, lecturers, and SIA managers at the UNM ICT Center. Data collection techniques used are observation, interviews, and documentation. The results of data analysis are presented in the form of a description that describes the procedures, constraints, and solutions in the use of the Academic Information System. The results showed that the effectiveness of the use of academic information systems in the Office Administration Education Study Program, Faculty of Social Sciences, Universitas Negeri Makassarwas classified as quite effective in terms of information quality indicators, namely accurate, timely, and relevant.